ANALISIS STRATEGI PENGHIMPUNAN DANA ZIS PADA PROGRAM PEDULI PENDIDIKAN DI DT PEDULI SUMUT - Ellya Fatmasari; Marliyah (CV. ADIBA AISHA AMIRA, 2023)
The purpose of this article is to examine the funding strategy implemented by Zis for the Care Education Program at Dt. Care for North Sumatra. Raising ZIS funds for the Education Program at DT Peduli North Sumatra can support the realization of an education system in the community, especially for underprivileged children. Children who are prioritized as ZIS recipients are classified as follows: (1) poor, orphaned (2) Muslim (3) still in school (4) have a certificate of indigency from the local RT (5) as well as children who classified as smart with proof of report cards that have been submitted to the DT Peduli North Sumatra team (6) domiciled in North Sumatra. After that, the DT Peduli North Sumatra team will follow up by surveying the field directly after the data on recipients of educational assistance is received (Documentation). The research methodology used is a qualitative approach. DT Peduli Medan aims to allocate zakat funds effectively by distributing them to mustahik with diverse financial backgrounds. Various resources such as financial capital, tangible assets, equipment, and human labor are all available. Furthermore, the leadership of DT Peduli Medan carried out socialization of philanthropic efforts aimed at encouraging the socio-economic progress of local communities in various fields, including education, economics, health, culture and other related fields.